HUBUNGAN PENGGUNAAN KONTRASEPSI HORMONAL DENGAN KEJADIAN KANKER PAYUDARA DI RSUD EMBUNG FATIMAH KOTA BATAM TAHUN 2017 - Mardhiah, Ainul; Anjani, Arum Dwi (Universitas Batam, 2019)
Cancer disease in Indonesia is the 5th cause of death and has significantly increased. The highest cancer risk in Indonesia is breast cancer which attacked women. This research aims to unravel the relation between the use of hormonal contraception and the occurrence of breast cancer. Analytical survey research design of cross sectional approach was used. The population was women visiting polycystic oncology and suffering breast cancer, sampling techniques used was accidental sampling. Research period was May to July 2017, the research instrument used checklist list. Data analysis was by using Chi Square, the result of this study show that there is a relation between hormonal contraceptive user and the breast cancer occurrence, p value = 0,00 (<0,05). In conclusion there is a significant relation between the use of contraception and breast cancer occurrence in RSUD Embung Fatimah Batam 2017. Suggestion for RSUD Embung Fatimah is to provide education on hormonal contraceptives.